O processo de readaptação funcional e suas implicações no gerenciamento em enfermagem - Batista, Joseli Maria; Juliani, Carmen Maria Casquel Monti [UNESP]; Ayres, Jairo Aparecido [UNESP] (FapUNIFESP (SciELO), 2010)
There is currently an increased interest in workers' health. Retraining due to illness is the topic of this study. The objective of this qualitative study was to understand how individuals cope with job retraining in a public hospital, utilizing interviews to understand how nursing professionals coped with the retraining process, which were then analyzed using Content Analysis as proposed by Bardin. The responses revealed problems in several areas of nursing work: Work Organization, Teamwork, Sick leave and retraining, and Team Management, altogether generating suggestions for improving the work experience in retraining. The retraining process generated individual, professional and social feelings of incompetence and guilt for workers. Important reflection and attitude changes are urgently needed, supporting team management, which will consequently improve care provided to the public.
Retraining due to illness ant its implications in nursing management
Keywords: Health manpower; Management; Nursing; Occupational health